The Adaptation of MCF-7 Breast Cancer Spheroids to the Chemotherapeutic Doxorubicin: The Dynamic Role of Phase I Drug Metabolizing Enzymes - Daniel Crispim; Carolina Ramos; Francisco Esteves; Michel Kranendonk (Metabolites)
Background/Objectives: Drug resistance (DR) is a major challenge in cancer therapy, contributing to approximately 90% of cancer-related deaths. While alterations in drug metabolism are known to be key drivers of DR, their role—particularly in the early stages of acquired chemoresistance—remains understudied. Phase I drug-metabolizing enzymes (DMEs), especially cytochrome P450s (CYPs), significantly influence the metabolic fate of chemotherapeutic agents, directly affecting drug response. This study aimed to investigate the role of Phase I DMEs in the early metabolic adaptation of breast cancer (BC) MCF-7 cells to doxorubicin (DOX). Methods: Four types of spheroids were generated from MCF-7 cells that were either DOX-sensitive (DOXS) or adapted to low concentrations of the chemotherapeutic agent (DOXA 25, 35, and 45 nM). The expression levels of 92 Phase I DMEs and the activities of specific CYP isoforms were assessed in both DOXS and DOXA spheroids. Results: A total of twenty-four DMEs, including fifteen CYPs and nine oxidoreductases, were found to be differentially expressed in DOXA spheroids. Pathway analysis identified key roles for the differentially expressed DMEs in physiologically relevant pathways, including the metabolism of drugs, arachidonic acid, retinoic acid, and vitamin D. Conclusions: The deconvolution of these pathways highlights a highly dynamic process driving early-stage DOX resistance, with a prominent role of CYP3A-dependent metabolism in DOX adaptation. Our findings provide valuable insights into the underlying molecular mechanisms driving the early adaptation of MCF-7 cells to DOX exposure.